Self-Concept and Learning Achievement of Mathematics Education College Student - Baiduri, Baiduri (Journal of Psychological Perspective, 2022)
Self-concept is one important factor in one's success, especially in education. This study aims to describe and analyze the relationship between students' self-concept in learning mathematics and mathematics learning achievement, and investigate the significance of differences in self-concept and learning achievement in mathematics education students seen from that semester. A total of 151 mathematics education students at the Teaching and Education Faculty of the University of Muhammadiyah Malang were used as participants in this study. Self-concept data and mathematics learning achievement were obtained through an online questionnaire using Google Forms. Descriptive statistics, correlation tests, and ANOVA tests were used in analyzing the data. Descriptions of self-concept and student achievement are presented per category and semester. Correlational analysis shows a very weak relationship between self-concept and student achievement. The results of the ANOVA test prove that there is no significant difference in self-concept in terms of student semesters. As for learning achievement there is a significant difference based on student semester.